Symbolism in Poe's "The Haunted Palace" - Kuhon, Fiola (Academic Journal Perspective: Education, Language, and Literature, 2018)
ABSTRACT Poetry always has a unique charm that captivates and draws the reader into its figurative world. One of the most interesting charm is symbolism used by the poet, in one single word lays a deeper explanation beyond what is perceptible by the eyes. Therefore, the aim of this research was to reveal the symbolism in â€œThe Haunted Palaceâ€, a gothic-themed poetry written by a well-known poet Sir Edgar Allan Poe. Having analyzed this poetry, the writer later found that Poeâ€™s â€œThe Haunted Palaceâ€ has some unique symbols used by the poet himself. Despite of writing long and descriptive lines, the poet chose appropriate symbols that lead the readers to think and conjecturing more deeply. Every symbol used in â€œThe Haunted Palaceâ€ represents simplicity, authenticity and brilliancy of Poe himself. Thus, a symbolism holds a very important role of poetry. It is not only pleasantly presented but also elucidating things beyond its literal substance. It proves that Poeâ€™s â€œThe Haunted Palaceâ€ is pleasant to be read but difficult to be interpreted. Keywords: poetry, symbolism, The Haunted Palace, Edgar Allan Poe Â 